Can information and communications technology applications contribute to poverty reduction? Lessons from rural India - Simone Cecchini and Christopher Scottb (Information Technology for Development 10 (2003) 73-84 73, 2003)
Information and Communications Technology (ICT) can reduce poverty by improving poor people's access to education, health, government and financial services. ICT can also help small farmers and artisans by connecting them to markets. It is clear that in rural India -as well as in much of the developing world- realization of this potential is not guaranteed. This paper outlines a simple model to explain why a digital divide may exist between rich and poor. Low-cost access to information infrastructure is a necessary prerequisite for the successful use of ICT by the poor, but it is not sufficient. The implementation of ICT projects needs to be performed by organizations and individuals who have the appropriate incentives to work with marginalized groups. Furthermore, grassroots intermediaries and the involvement of the community are identified as the key factors that foster local ownership and the availability of content and services that respond to the most pressing needs of the poor.